2020
DOI: 10.1186/s13550-020-00689-z
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of [18F]EF5-PET/CT to image hypoxia in ovarian tumors: a clinical study

Abstract: Rationale Evaluation of the feasibility of [18F]EF5-PET/CT scan in identifying hypoxic lesions in ovarian tumors in prospective clinical setting. Methods Fifteen patients with a suspected malignant ovarian tumor were scanned with [18F]EF5 and [18F]FDG-PET/CT preoperatively. The distribution of [18F]EF5-uptake, total intraabdominal metabolic tumor volume (TMTV), and hypoxic subvolume (HSV) were assessed. Results [18F]EF5-PET/CT suggested hypoxia in 47% (7/15) patients. The median HSV was 87 cm3 (31% of TMTV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hypoxia is a common condition reported in several cancers, with 50% to 60% of solid tumors exhibiting hypoxic regions. 25 This metabolic alteration acts as a driver of cancer progression. Hypoxia can enhance the expression of GLUT5, as HIF-1α is tightly associated with GLUT5 in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a common condition reported in several cancers, with 50% to 60% of solid tumors exhibiting hypoxic regions. 25 This metabolic alteration acts as a driver of cancer progression. Hypoxia can enhance the expression of GLUT5, as HIF-1α is tightly associated with GLUT5 in BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation for the difficulty in using 18 F-EF5 PET to quantify hypoxia in clinical prostate tumours is the diffuse nature of prostate cancer within the prostate gland. Rather than a single tumour mass as is typical of solid tumour types that exhibit high 18 F-EF5 T/M ratios that indicate tumour hypoxia [17][18][19][20][21], prostate tumours tend to be multi-focal, with cancerous cells interspersed throughout the prostate. Since hypoxic tumour cells make up only a fraction of tumour cells in a given lesion, quantifying 18 F-EF5 uptake in a fraction of prostate tumour cells may be limited by the detection sensitivity of PET.…”
Section: Discussionmentioning
confidence: 99%
“…EF5 has been extensively used in pre-clinical studies across many tumour types to label and quantify hypoxic tumour cells and has shown promising results in clinical settings with head and neck cancer, including correlation with patient outcome [17]. PET measurement of 18 F-EF5 uptake has been used to quantify tumour hypoxia in lung cancer [18], head and neck cancer [17,19,20], and ovarian cancer [21]. Yapp et al previously found 18 F-EF5 PET to effectively detect hypoxia in the Shionogi model of prostate cancer, in both the androgen-dependent and independent phases of the model [22,23], but 18 F-EF5 PET has yet to be tested for detecting hypoxia in clinical prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]-EF5 was studied in NSCLC and the tracer uptake was correlated to tumor hypoxia ( 105 , 106 ). This tracer was studied in ovarian cancers but this indication appeared to be limited due to the relatively weak uptake in tumors and the biliary excretion may impose limitations on assessing hypoxic tumors located near to the intestine ( 107 ). The injected dose is usually 4 MBq/kg or a fixed activity of 300 MBq.…”
Section: Medical Imagingmentioning
confidence: 99%